Improving the bandwidth of microstructured multimode W-type POFs in the visible light range - Drljača, Branko; Simović, Ana; Djordjevich, Alexandar; Aidinis, Konstantinos; Savović, Svetislav (Frontiers in Physics, 2025)
The bandwidth of multimode W-type microstructured plastic optical fibers (mPOFs) is analyzed using the time-dependent power flow equation (TD PFE). The results demonstrate that increasing the wavelength enhances the bandwidth in W-type mPOFs, depending on the inner cladding width and the launch beam distribution width. We observed that bandwidth improves with thinner and shallower inner cladding, as well as a narrower centrally launched beam. This characterization aligns with the fibers’ effectiveness in increasing bandwidth, allowing for the customization of various W-type optical fibers for specific applications at different wavelengths.